Sports-related injuries in New Zealand: National Insurance (Accident Compensation Corporation) claims for five sporting codes from 2012 to 2016 - King, D.; Hume, P. A.; Hardaker, N.; Cummins, C.; Gissane, C.; Clark, T. (British Journal of Sports Medicine, 2019)
Objectives: To provide epidemiological data and related costs for sport-related injuries of five sporting codes (cricket, netball, rugby league, rugby union and football) in New Zealand for moderate-to-serious and serious injury claims.